Impact of a Stewardship Initiative to Decrease Treatment of Asymptomatic Bacteriuria and Pyuria in the Emergency Department. (4th October 2017) - Smith, Jessica; Williamson, John; Johnson, James; Hannum, Jennifer; Ohl, Christopher; Luther, Vera; Beardsley, James
Abstract: Background: Antibiotic treatment of asymptomatic bacteriuria (AB) provides no benefit and can lead to negative outcomes. The impact of asymptomatic pyuria (AP) on antibiotic use is not well characterized, nor is the impact of treating AB/AP in the emergency department (ED). The purpose of this study was to determine whether a multi-faceted stewardship initiative decreased unnecessary antibiotic treatment of AB/AP in the ED of an 885-bed academic medical center. Methods: Beginning in Dec 2015, a series of interventions were implemented, including inservices, pocket cards, electronic order entry alerts, and elimination of reflex urine cultures for abnormal urinalyses. Patients discharged from the ED in Aug-Oct 2015 (pre-intervention group) and Dec 2016-Feb 2017 (post-intervention group) were consecutively screened retrospectively. Asymptomatic patients ≥18 yrs old with ≥10 5 CFU/mL organisms on urine culture or >12 WBC/hpf on urinalysis were included. Patients with pregnancy, separate infection requiring antibiotics, immunocompromised state, paraplegia, neurogenic bladder, or altered genitourinary anatomy were excluded. The primary outcome was the proportion of patients with AB and/or AP prescribed antibiotics within 72 hours of ED discharge. Secondary outcomes were the number of urine cultures ordered in the ED and the number of patients returning to the ED with symptomatic urinary tract infection (UTI) within 30 days. 32 patients in each group were required to achieve 80% power, assuming 30% difference in primary outcome. Results: 74 patients met study criteria (37 in each group). 52 patients (70%) had AP without AB. Antibiotic treatment and the number of urine cultures ordered decreased significantly in the post group. Conclusion: A multi-faceted stewardship initiative significantly decreased treatment of AB/AP in the ED. AP appears to contribute significantly to unnecessary antibiotic use in the ED and would be a valid target for stewardship initiatives. Disclosures: All authors: No reported disclosures.